2015
DOI: 10.1186/s40201-015-0216-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Effects of Nano-particles on Histo-pathological changes of the fish

Abstract: Regarding fast development of the nanotechnology and the probably of it’s side effects on aquatic body organs, this study investigate the effects of nanosilver administration on histology of gill, kidney and biochemical parameters in common carp. The silver nanoparticles were synthesized in a one-step reduction process in an aqueous solution. 60 O. mykiss were obtained from a local commercial hatchery. Fish were divided randomly into four groups. Control group was kept in dechlorinated tap water without any ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…ALT and AST are considered to be important parameters for assessing tissue injury or organ dysfunction. Liver is the major organ where these enzymes are generally found, and their increased level shows cellular toxicity [63]. An increase in ALT and AST levels was in accordance with our histopathological results of kidney and liver damage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…ALT and AST are considered to be important parameters for assessing tissue injury or organ dysfunction. Liver is the major organ where these enzymes are generally found, and their increased level shows cellular toxicity [63]. An increase in ALT and AST levels was in accordance with our histopathological results of kidney and liver damage.…”
Section: Discussionsupporting
confidence: 90%
“…An increase in ALT and AST levels was in accordance with our histopathological results of kidney and liver damage. Monfared et al [ 63 ] also mentioned an increase in cholesterol, ALT, and AST in AgNP-exposed rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason why a chronic toxicological study was not performed is precisely because of the observed antiviral effect. Fabrega et al (2011), points out that invertebrates such as water flea Daphnia pulex, acute and chronic toxicity studies do not generate bioaccumulation, although other authors point out that in the event that AgNPs accumulate in the gills, they do not have harmful side effects (Xiang et al, 2019), however, this could dependent of administered doses (Monfared et al, 2015). It is important to mention that more experiments should be carried out to consider the possibility of applying this nanoparticular design in the field.…”
Section: Discussionmentioning
confidence: 99%
“…However, that may not apply to NPs. In gills, evaluation of NPs effects have been performed mainly by histopathology (1923, 25, 28, 3033, 39, 40), NP bioaccumulation (21, 23, 24, 27, 32, 34, 37, 39) and measurement of oxidative stress biomarkers (19, 22, 24, 25, 29, 30, 34, 35, 37, 39, 41) (refer to Oxidative stress section and Table 1). Regarding histopathology, some inaccurate histopathology-based results have been published due to the high degree of expertise necessary (122).…”
Section: External Barriersmentioning
confidence: 99%